Photoluminescence Studies of Stillwellite type Eu, Ho, Er co-doped Lanthanum Borosilicate Up Conversion Luminescent Materials for Solar Energy Applications - Karthikeyani, A.; Sathriya, N.; Anbukumaran, K. (University of Jaffna, 2019)
In the present study, a new luminescent stillwellite type lanthanum borosilicate (doped with Eu3+ and co- doped with either Er3+/Ho3+ or both) up-conversion materials were synthesized and characterized by photoluminescence studies. Using Eu3+ luminescence as a local probe, the microscopic symmetry around it in the host matrix is studied. Two cationic sites were found to exist. Co-doping of Er3+ and /Ho3+, has altered the PL line spectrum of Eu3+ into a broader one which could be explained based on carrier energy transfer model and this broadening is a proof for the existence of up conversion property in the new materials synthesized. Further, a blue shift is observed in the PL emission spectra by progressively increasing the excitation wavelength from 240 nm to 270 nm which, also infers the presence of successful up-conversion property in the newly developed material
Keywords: Upconversion materials; Solar energy application; quantum efficiency enhancement; stillwellite type materials; photon up-conversion; luminescent materials; blue shift